Pemahaman Fiqih Ibadah Masyarakat Desa Buduran RT 22 Kecamatan Tanon Kabupaten Sragen Terhadap Pelaksanaan Puasa Ramadhan - Almaidah Yogi Mahanani; Devi Nurul Affla; Qodim Ma’shum (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to examine the level of understanding of fiqh of worship among the community of Buduran Village RT 22, Tanon District, Sragen Regency, particularly in relation to the implementation of Ramadhan fasting. The research applies a qualitative descriptive method with a field research approach, allowing the researcher to directly observe and explore community practices. Data were collected through observation, interviews, and documentation to obtain comprehensive and accurate findings. The results indicate that the community’s understanding of the laws and requirements of Ramadhan fasting is generally adequate, although some individuals still lack deeper comprehension. In addition, understanding of actions that invalidate fasting varies among community members, showing differences in knowledge and interpretation. The implementation of the pillars and sunnah practices of fasting has been carried out relatively well; however, certain practices are still not fully aligned with established fiqh guidelines. Furthermore, factors such as educational background, social environment, and access to Islamic learning activities significantly influence the level of understanding within the community. Overall, this study highlights the importance of continuous religious education to improve the quality of worship practices.